Fouiller l’écrit. Témoignage - Philippe Artières (L'Atelier du CRH)
This text takes the form of a tribute-homage. It goes back over the reading proposed by Daniel Fabre of the Pierre Rivière dossier in an article published in the Journal Le Débat, and more generally over the analysis of this case in his career as an anthropologist. The author shows how, through this file, D. Fabre interacted with M. Foucault as well as with R. Allio, the author of a filmic adaptation of the history of this parricide. This tribute finally tries to account for the singular way in which Fabre worked, nourishing dossiers opened by others and acting himself as a relay